Strategy of Education Provider Organizations in Utilizing Digital Literature (Study at IT Baitul Muslim High School, East Lampung, Indonesia) - Saputra, Pindo Riski; Munawaroh, Kholifatul (Journal of Research in Social Science and Humanities, 2022)
Advances in technology and information have opened up great opportunities for the community, especially for the world of education. Therefore, educational institutions or organizations must have strategies in dealing with changes in student interaction patterns on information technology devices and how schools face the development of the digital era. This research is a research that explores the strategy of education providers in the use of digital literacy as a medium to improve the quality of learning. The research method used in this research is descriptive qualitative analysis with a qualitative approach that focuses on substantive and formal theories as well as events that exist and are recognized as true. The strategy of the education provider organization in utilizing digital literacy at the IT Baitul Muslim High School in East Lampung has been going well so far, because the digital literacy program had been implemented in the school environment long before the COVID-19 pandemic hit. So that the learning process with digital literacy is nothing new for schools and students. Although in this case the improvement of teacher competence continues to be pursued as one of the school's strategies to improve teacher competence to actualize learning and the potential of students in digital literacy learning